2013
DOI: 10.1212/01.wnl.0000436945.01023.ac
|View full text |Cite
|
Sign up to set email alerts
|

De novo mutations in hereditary diffuse leukoencephalopathy with axonal spheroids (HDLS)

Abstract: Typical clinical phenotype and early brain MRI alterations can help to guide the diagnosis of HDLS. Because we confirmed de novo mutations in one-third of patients with CSF1R mutations, this diagnosis should be considered even in the absence of a family history. Furthermore, we present evidence for reduced penetrance of a CSF1R mutation. These results have substantial impact for genetic counseling of asymptomatic individuals at risk and should foster research into disease-modifying factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 18 publications
1
57
0
1
Order By: Relevance
“…The median age of onset is 42 ± 13 years (range 8-78) with a disease duration of 5 ± 7 (range 1-34) years that is unrelated to the time of onset (Ahmed et al, 2013; Freeman et al, 2009; Guerreiro et al, 2013; Hoffmann et al, 2014; Karle et al, 2013; Kinoshita et al, 2014; Kleinfeld et al, 2013; Kondo et al, 2013; Konno et al, 2014; Mitsui et al, 2012; Rademakers et al, 2011; Sundal et al, 2012; Van Gerpen et al, 2008; Wider et al, 2009). Symptoms may vary according to gender (Hoffmann et al, 2014), and clinical presentation is variable.…”
Section: Discussionmentioning
confidence: 99%
“…The median age of onset is 42 ± 13 years (range 8-78) with a disease duration of 5 ± 7 (range 1-34) years that is unrelated to the time of onset (Ahmed et al, 2013; Freeman et al, 2009; Guerreiro et al, 2013; Hoffmann et al, 2014; Karle et al, 2013; Kinoshita et al, 2014; Kleinfeld et al, 2013; Kondo et al, 2013; Konno et al, 2014; Mitsui et al, 2012; Rademakers et al, 2011; Sundal et al, 2012; Van Gerpen et al, 2008; Wider et al, 2009). Symptoms may vary according to gender (Hoffmann et al, 2014), and clinical presentation is variable.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, white matter changes have been observed in elderly asymptomatic mutation carriers. 20,21 Additionally, the calcifications may diminish along while white matter pathology progresses. However, to elucidate the mechanism by which CSF1R mutations cause such unique calcifications, further investigation is still required.…”
Section: Discussionmentioning
confidence: 99%
“…The sarcoidosis patients were studied before diagnostic bronchoscopy and before any treatment with glucocorticoids. HDLS cases 693, 745, and 766 have been described in Schuberth et al, 18 and case 667 was reported in Karle et al 19 The study was approved by the local ethics committee of the Ludwig-Maximilians-Universität München.…”
Section: Blood Samplesmentioning
confidence: 99%